Sustainability in Food Consumption and Food Security - Popp, József H.c; Lakner, Zoltán; Oláh, Judit (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The transformation of food chains towards sustainability in food consumption and food security is a global issue, connected with the global challenges of poverty reduction, employment and urbanization. Combating malnutrition-undernutrition and micronutrient deficiencies-as well as overweight and obesity is an increasing problem. The main topics to be examined are the following: Ensuring sustainable food production (land and sea), sustainable diets and sustainable communities, including issues for agricultural transformation in face of increasing competition for land use; promoting healthy food systems and increasing the focus on nutrition, with multiple implications for diet quality, vulnerable groups, and informed choice; biotechnology could play an important role in climate change mitigation (e.g., nutrient-efficient plants) and adaptation (e.g., drought-tolerant plants), renewable energies, biodegradable products, rural development, and global food security; identifying the means to promote resilience, including resilience in ecosystems and in international markets; responding to climate change and other environmental and social change. The focus should also cover issues for vulnerable groups such as mothers and children, the elderly, patients, and migrants to understand the general aspects of consumer behavior. Sustainability related to product standards and reactions of consumers to these standards are also of great importance.